S100A10 Accelerates Aerobic Glycolysis and Malignant Growth by Activating mTOR-Signaling Pathway in Gastric Cancer - Li, Yan; Li, Xiao-Yu; Li, Li-Xiang; Zhou, Ru-Chen; Sikong, Yinhe; Gu, Xiang; Jin, Bi-Ying; Li, Bing; Li, Yan-Qing; Zuo, Xiu-Li (Frontiers in Cell and Developmental Biology, 2020)
S100 calcium-binding protein A10 (S100A10) is crucially involved in the tumorigenesis of multiple malignant tumors. Reprogrammed glucose metabolism is emerging as a hallmark of various human cancers. However, the function of S100A10 in aerobic glycolysis is unclear. The expression of S100A10 was analyzed using the Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA), The Cancer Genome Atlas (TCGA), and the UALCAN cancer database. Prognostic analysis was performed using the Kaplan–Meier Plotter. The correlation between S100A10 and key glycolytic factors was assessed by GEPIA. The glycolysis level was examined by determining glucose consumption, lactate production, adenosine triphosphate production, cellular oxygen consumption rate, and extracellular acidification rate. Cell apoptosis was investigated by flow cytometry. Colony formation and BrdU assays were performed to detect cell proliferation. A subcutaneous xenograft mouse model was established to evaluate the effects of S100A10 in vivo. Gene Set Enrichment Analysis and western blotting were performed to explore the downstream signaling pathway. S100A10 was significantly upregulated in gastric cancer. Its expression was associated with poor survival. S100A10 increased glucose consumption, lactate production, and the switch from oxidative phosphorylation to aerobic glycolysis. S100A10 promoted malignant proliferation and suppressed cell apoptosis in gastric cancer. S100A10 activated the mTOR pathway by interacting with annexin A2 (ANXA2) to accelerate tumor glycolysis, resulting in tumor malignant progression. S100A10 contributed to aerobic glycolysis and accelerated malignant growth by modulating the Src/ANXA2/AKT/mTOR signaling pathway. Thus, S100A10 may have pivotal roles in gastric cancer.